Peningkatan Keterampilan Menulis Karangan Narasi Melalui Strategi Index Card Matchdengan Menggunakan Big Book pada Siswa Kelas V di SD N 2 Kemiri Tahun Pelajaran 2015/2016 - Mayasofa, Hilda Ajeng, Dra. Risminawati, M.Pd (2016)
Big book a story book that has big in size and has pictures and tells stories. Big book functions as a media to facilitate students learning. This research aims: 1) to increase skill writing of narrationthrough index card match strategy by using big book in fifth grade students of SDN 2 KemiriSubdistrictGubug, of Regency Grobogan, 2) to increase learning result in narration writing skill through index card match strategy by students of SDN 2 KemiriSubdistrictGubug of Regency Grobogan . The research method is Class Room Action Research. The research subjects is teacher and 25 students in fifth grades in SDN 2Kemiri on 2015/2016 year. The collection of document obtained from test results, observation, documentation, and interview. Data analysis tehnigue used is interactiveanalysis. This increase from the research sill writing narrarion from index card match strategy with using a big book. narration writing skill increase can are: the result is the average score of pra-siklus is 27%, average of cycleis 53%, average of cycle II is 81% and score study skill writing increase is: The result of students learning of pra-cycle is 8 students or 32%, average of cycle I is 18 students or 72%, and average of cycle II is 21 students or 84%.